ЖРТВОВАЊЕ ЖИВОТИЊА У ГОДИШЊЕМ КАЛЕНДАРУ СРБА (Prilozi za književnost, jezik, istoriju i folklor, 2023)
In ritual practice, which is the part of the celebration of annual holidays, Serbs usually choose different types of animals. Thus, a pig is most often sacrificed on Christmas, on St. George’s Day – a lamb, on St. Elijah – a rooster, on St. Mrata – chicken, etc. The ritual slaughter of a certain animal, which is carried out by the wider community on a certain day of the year, in the Bulgarian-Macedonian-Serbian area is known as kurban.The paper discusses which animal species are sacrificed on a particular holiday in the annual calendar. Regional variations or parallels were also observed (cases of sacrificing the same species on different holidays). Attention was paid to the way the animal was treated before the act of sacrifice, then the rite of sacrifice itself was analyzed (who performs it, in what place, at what time, in what way), as well as its purpose. Also, later procedures with the sacrificed animal were analyzed and the role that is given to certain parts of the animal’s body